Calculation of shell element failure based on the state of stress inside of a neck: - Dragt, R.C.; Kraus, J.; Walters, C.L. (2015)
Simulation of failure in thin-walled structures is critical for the correct determination of crash performance of ships and offshore structures. Typically, shell elements are used, but these elements are not able to adequately capture local failure, especially inside of a neck. This paper addresses these gaps by adapting the Bridgman (1952) model of a neck inside of a plate by making it three-dimensional and offering an estimate of the relationship between state parameters of a shell element and the geometry inside of a neck. Finally, recommendations are also made about how to interface this information with the Modified Mohr-Coulomb failure locus to create a practical algorithm for assessing failure in shell elements.